O olhar dos idosos sobre as políticas públicas voltadas para a população idosa: uma análise do município de Ituiutaba (MG) - Gonçalves, Geisa Candida da Silva (2019)
In the last twenty years, the elderly population has grown substantially worldwide, and in Brazil this trend has also been verified. In Ituiutaba (MG), the growth of this population reached 4,52% in this period, so that 14.5% of the total population of the county fits this age rating. Such growth can easily be explained by the emergence of new medicines, vaccines and even people's lifestyles, rising other challenges for Brazilian society, causing family, social, urban and industrial transformations. To attend the new demands, the State presents public policies specifically aimed at the elderly in order to attend the needs of this population, in order to guarantee essential services to which citizens are entitled, ensuring them an aging with quality, tranquility and security. In a general context, the aim of this work is precisely to investigate the public policies aimed at the elderly population of Ituiutaba (MG), to verify the understanding of the elderly about these public policies and to indicate actions that contemplate the needs of this population. Therefore, interviews were done with an agent of Ituiutaba Elderly County Council (CMII), with a municipal manager linked to the Municipal Secretariat of Social Development (SEDS) and with the elderly people who participate in activities and projects performed by the six Centers of Reference and Social Assistance (CRAS) of the Ituiutaba City, mostly retirees surviving with up to two minimum wages. The results indicate that all respondents recognize the importance of CRAS in their lives, the excellent care they receive and the need to further improve their physical spaces. Although there are several public policies aimed at the elderly, there is a great difficulty for them to understand it and what rights are guaranteed by them. Another interesting and worth to mention result is the priority that the elderly attach to public transport and public health care, making it clear that these are the two most important “rights”, in detriment, for example, of family life. Anyway, it is evident the need to develop more research and actions that contribute to the valorization of the elderly, as well as their engagement in society and above all, the guarantee of an aging with quality and dignity.